Soft Skills or Hard Cash? The Impact of Training and Wage Subsidy Programs on Female Youth Employment in Jordan - Groh, Matthew; Krishnan, Nandini; McKenzie, David; Vishwanath, Tara (World Bank, Washington, DC, 2012)
Throughout the Middle East, unemployment rates of educated youth have been persistently high and female labor force participation, low. This paper studies the impact of a randomized experiment in Jordan designed to assist female community college graduates find employment. One randomly chosen group of graduates was given a voucher that would pay an employer a subsidy equivalent to the minimum wage for up to 6 months if they hired the graduate; a second group was invited to attend 45 hours of employability skills training designed to provide them with the soft skills employers say graduates often lack; a third group was offered both interventions; and the fourth group forms the control group. The analysis finds that the job voucher led to a 40 percentage point increase in employment in the short-run, but that most of this employment is not formal, and that the average effect is much smaller and no longer statistically significant 4 months after the voucher period has ended. The voucher does appear to have persistent impacts outside the capital, where it almost doubles the employment rate of graduates, but this appears likely to largely reflect displacement effects. Soft-skills training has no average impact on employment, although again there is a weakly significant impact outside the capital. The authors elicit the expectations of academics and development professionals to demonstrate that these findings are novel and unexpected. The results suggest that wage subsidies can help increase employment in the short term, but are not a panacea for the problems of high urban female youth unemployment.